Imbalance of oral microbiome homeostasis: the relationship between microbiota and the occurrence of dental caries - Rui Liu; Yingshuang Liu; Jialong Yi; Yanke Fang; Qiang Guo; Lei Cheng; Jinzhi He; Mingyun Li (BMC Microbiology)
Abstract Background Streptococcus mutans is recognized as a key pathogen responsible for the development of dental caries. With the advancement of research on dental caries, the understanding of its pathogenic mechanism has gradually shifted from the theory of a single pathogenic bacterium to the theory of oral microecological imbalance. Acidogenic and aciduric microbial species are also recognized to participate in the initiation and progression of dental caries. This study is designed to elucidate the relationship between oral microbiome dysregulation and the initiation of dental caries. Results 16 S rRNA gene sequencing of saliva and dental plaque from the Specific Pathogen Free Control group and the Specific Pathogen Free sucrose diet group revealed that a sucrose diet significantly influenced the composition of the oral microbiome. At the phylum level, the dominant microbial communities in both groups of mice were Firmicutes, Proteobacteria, Unclassified Bacteria, Actinobacteria, and Bacteroidetes. At the genus level, statistical analysis identified significant differences in the abundance of 18 genera between the two groups. The relative abundance of the Gemella genus was significantly increased in the SPF Sucrose group. The SPF Control group and the Germ-free Control group have no differential bacterial genera in the oral microbiome. Micro-CT examination of the mandibles revealed the development of dental caries in both the SPF Sucrose group and the Germ-free Sucrose group. Conclusions This study indicates that a dysbiotic microbial community can lead to the development of caries. Lays the foundation for further research into the etiology of dental caries.